Wanderings - Mercer, Leah; Brown Ash, Margi; Callaghan, Zac (The Nest Ensemble, 2024)
Wanderings directed and co-written by Leah Mercer with Margi Brown Ash and Zac Callaghan. Season premiered for DOOR 3 from 29 November – 14 December 2024 at the Diane Cilento Studio, Queensland Theatre. A confabulation of autobiography and fiction, Wanderings is a play about the challenges, demands and heart-opening opportunities of changing family dynamics and shifting identities through the eyes of a transgender son and his mother living with dementia. Wanderings embraces the universality of transitioning and the importance of connection while walking the line between humour and pathos, kindness and ferocity, fear and courage. The production received three 2024 Matilda Award nominations recognising excellence in the Queensland theatre industry, including: The Lord Mayor’s Award for Best New Australian Work; Best Performance in a Leading Role, Independent Production; and Best Set Design. Commissioned by Australian Plays Transform in partnership with the Pride Foundation Australia, Wanderings received support and investment from the following sponsors: Queensland Government through Arts Queensland; GreenHouse National Artists Residency (HotHouse Theatre); Queensland Theatre DOOR 3; Jelley Family Foundation; and Curtin University.